Modern domocracies - Bryce, James (London, 1921)
The term Democracy has in recent years been loosely used to denote sometimes a state of society, sometimes a state of mind, sometimes a quality in manners. It has become encrusted with all sorts of associations attractive or repulsive, ethical or poetical, or even religious. But Democracy really means nothing more nor less than the rule of the whole people expressing their sovereign will by their votes. It shows different features in different countries, because the characters and habits of peoples are different; and these features are part of the history of each particular country. But it also shows some features which are everywhere similar, because due to the fact that supreme power rests with the voting multi tude. It is of the Form of Government as a Form of Government that is to say, of the features which democracies have in common-that this book treats, describing the phenomena as they appear in their daily working to an observer who is living in the midst of found time to probe to the bottom. Even when one thinks a view unsound or a scheme unworkable, one must regard all honest efforts to improve this unsatis factory world with a sympathy which recognizes how many things need to be changed, and how many doctrines once held irrefragable need to be modified in the light of supervenient facts. What we want to-day is a better comprehension by each side in economic controversies of the attitude and arguments of the other. Reconcile ments are not always possible, but comprehension and appreciation should be possible.
Keywords: Domocracies